1980
DOI: 10.1159/000250493
|View full text |Cite
|
Sign up to set email alerts
|

Richner-Hanhart Syndrome and Tyrosinemia Type II

Abstract: A patient already published as a case of Richner-Hanhart syndrome (RHS) (stabilized corneal lesions and hyperkeratotic lesions on the palms and soles) proved to be associated with tyrosinemia type II. 2 other cases (sister and brother) with only typical dermatologic features of RHS and tyrosinemia type II are described. The treatment with a low phenylalanine and tyrosine diet improves the cutaneous lesions in our 3 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Penetrance of oculocutaneous manifestation varies in severity and age at onset (Richner t938;Waardenburg et al 1962;Hunziker 1980) and type II tyrosinaemia patients with cutaneous signs may not have the ocular lesions (Reh~tk et al 1981). Onset of eye signs tends to be later than that of skin signs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penetrance of oculocutaneous manifestation varies in severity and age at onset (Richner t938;Waardenburg et al 1962;Hunziker 1980) and type II tyrosinaemia patients with cutaneous signs may not have the ocular lesions (Reh~tk et al 1981). Onset of eye signs tends to be later than that of skin signs.…”
Section: Discussionmentioning
confidence: 99%
“…Exacerbation of all skin manifestations in the winter months is also a new finding. The patient learned to tolerate a low-tyrosine diet and the oculocutaneous signs have improved when tyrosine levels are lower; others have observed this effect (Garibaldi et al 1977;Hunziker 1980). Some believe that the clinical manifestations in type II hypertyrosinaemia may reflect intracellular tyrosine levels (Bohnert and Anton-Lamprecht 1982) but there is no satisfactory metabolic explanation yet for variability in expression of the clinical disease.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the patients described by Rimbaud et al [17], Salamon and Lazovic [18] and Salamon [19], whose tyrosinemia is not report ed, may be clinically considered as RichnerHanhart syndrome [20] and might be proven to be tyrosinemia type II. Interest ingly, at least 9 patients out of the 14 collect ed by Franceschetti et al [8] were subse quently found to have high amino acid blood levels [21][22][23][24][25][26]…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhidrosis may be associated with hyperkeratosis. 10 Leukokeratosis of the tongue has been reported. 11 The pain in the soles may be severe enough to prevent ambulation.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis can easily be established by high plasma levels of tyrosine, with other plasma amino acid levels being normal. 10,17 Tyrosine is the only amino acid increased in the urine of these patients. TAT activity is reduced or absent in supernatant of liver homogenates.…”
Section: -16mentioning
confidence: 94%